Multimarker Panels for Detection of Early Stage Hepatocellular Carcinoma: A Prospective, Multicenter, Case‐Control Study. Issue 4 (19th November 2021) - Piratvisuth, Teerha; Tanwandee, Tawesak; Thongsawat, Satawat; Sukeepaisarnjaroen, Wattana; Esteban, Juan Ignacio; Bes, Marta; Köhler, Bruno; He, Ying; Swiatek‐de Lange, Magdalena; Morgenstern, David; Chan, Henry Lik‐Yuen
Abstract : Hepatocellular carcinoma (HCC), the sixth most common cancer worldwide, has an incidence rate equal to mortality. Over 80% of HCC cases occur within a high‐risk population, mainly patients with both cirrhosis and chronic hepatitis B or C. With a 5‐year survival rate ranging from <16% for advanced HCC to >90% for early stage HCC, there is a high medical need for the early detection of HCC. In this study, we systematically evaluated biomarkers mentioned in international guidelines and peer‐reviewed literature for HCC surveillance and diagnosis with the aim of identifying combinations that display high sensitivity and specificity for early stage HCC. Fifty biomarkers were measured in the first sample panel, panel A (n = 110), and subjected to univariate analysis. Of these, 35 biomarkers (38 assays) from panel A and an additional 13 biomarkers from the literature were prioritized for subsequent multivariate evaluation with lasso regression and exhaustive search of two‐ to four‐biomarker combinations (panel B). Panel B included 1, 081 samples from patients with HCC (n = 308) or with chronic liver diseases (n = 740). Among all patients, 61.0% had hepatitis B, 32.9% had hepatitis C, and 60.5% had cirrhosis; 40.6% of patients with HCC had early stage cancer. Protein induced by vitamin K absence‐II (PIVKA‐II; also known as des‐gamma‐carboxy prothrombin [DCP]) and alpha‐fetoprotein (AFP) demonstrated the best clinical performance, both individually and in combination, and the addition of a third biomarker ( Lens culinaris agglutinin‐reactive fraction of AFP [AFP‐L3], cartilage oligomeric matrix protein [COMP], insulin‐like growth factor‐binding protein 3 [IGFBP3], or matrix metalloproteinase 3 [MMP3]) further increased sensitivity for the detection of both early stage and all‐stage HCC. The addition of age and sex to the three‐biomarker panel resulted in an improved diagnostic performance. Conclusion: The combination of AFP and PIVKA‐II, with either IGFBP3, COMP or MMP3, plus age and sex, demonstrated the best performance for the detection of early‐ and all‐stage HCC. These novel panels performed similar to that of the GALAD score (sex [gender], age, plus serum levels of AFP, AFP‐L3 and DCP [PIVKA‐II]), a promising screening tool developed for HCC detection. Abstract : image